Determination of six groups of mycotoxins in Chinese dark tea and the associated risk assessment. (June 2020) - Ye, Ziling; Wang, Xu; Fu, Ruiyan; Yan, Hangbin; Han, Sanqing; Gerelt, Khishigjargal; Cui, Pu; Chen, Jingjing; Qi, Kezong; Zhou, Yu
Abstract: Chinese dark tea is widely enjoyed for its multiple health-promoting effects and pleasant taste. However, its production involves fermentation by microbiota in raw tea, some of which are filamentous fungi and thus potential mycotoxin producers. Accordingly, whether mycotoxins pose health risk on dark tea consumption has become a public concern. In this study, a cleaning method of multi-functional column (MFC) and immunoaffinity column (IAC) in tandem combined to HPLC detection was developed and validated for determining ten mycotoxins of six groups (i.e., aflatoxins of B1, B2, G1 and G2, ochratoxin A, zearalenone, deoxynivalenol, fumonisins of B1, B2, and T-2) in dark teas. The interferences from secondary metabolites were effectively reduced, and the sensitivities and recoveries of the method were qualified for tea matrices. Six groups mycotoxins were determined in 108 samples representing the major Chinese dark teas by using the new method. Subsequently, the dietary exposure and health risks were evaluated for different age and gender groups in Kunming and Pu'er in China and Ulan Bator in Mongolia. The occurrence of zearalenone was 4.63% and that of ochratoxin A was 1.85%, with the other four groups mycotoxins were below the limits of quantification. The hazard index values for the five groups' non-carcinogenic mycotoxins were far below 1.0. The deterministic risk assessment indicated no non-carcinogenic risks for dark tea consumption in the three areas. Probabilistic estimation showed that the maximum value of 95th percentile carcinogenic risk value for the aflatoxins was 2.12 × 10 −8, which is far below the acceptable carcinogenic risk level (10 −6 ). Hereby, six groups mycotoxins in Chinese dark tea showed no observed risk concern to consumers. Graphical abstract: Image 1 Highlights: A MFC-IAC-HPLC method was developed and validated for mycotoxins determination in dark tea. Tea matrix interference was effectively reduced by MFC-IAC in tandem. Multiple mycotoxins contamination was determined. Multiple mycotoxins dietary risk was assessed on Chinese dark tea. Abstract : Six groups of mycotoxins determination methods on dark tea matrices were developed, and mycotoxins dietary risk from Chinese dark tea was assessed.